The door in the forest - Townley, Rod (Alfred A. Knopf, 2011)
While trying to outwit the soldiers who are occupying their small town, fourteen-year-old Daniel, who cannot lie, and Emily, who discovers she has magical powers, are inexplicably drawn to a mysterious island in the heart of the forest where townsfolk have been warned never to go.